AJAX next level (authentication, servers, modules, projects, and more). (Packt Publishing, 2022)
AJAX allows your users to add/delete/view/update content, post comments, submit reviews, submit forms, and a ton more, without getting a page refresh. This course will captivate you with real-life examples and catapult you to the next level and set you well on your way to achieving everything you want to with AJAX. This course introduces you to AJAX and lays the foundation. Later on, you will start digging into advanced concepts such as Basic Auth, CORS, and servers. In this course, you will learn how to send authentication information using the XHR object and the Fetch API. You will see how to take user inputs, convert them into JSON data, and send that data to a server. Understand how to retrieve XML, JSON, and text data from a server. Look at how to take data from the server and update the page dynamically using JavaScript. You will also learn how to write great code using modules, write middleware and define RESTful AJAX APIs, and more. Finally, you will build a fully functional site that performs basic CRUD operations and saves data to a server. This simple application will use the power of RESTful AJAX APIs to speak to a server and perform tasks like adding/deleting/updating and viewing data that is stored on your server. By the end of this course, you will be able to "speak" and "walk" AJAX by gaining an understanding of how you can use it in meaningful and practical ways. What You Will Learn Learn how to send authentication information using XHR and Fetch Check how to set up an Apache server, a PHP server, and a Node server Understand RESTful APIs and set up a server to store all of your data Learn to access JSON and text data from a server response Listen for the DOMContentLoaded event to send an AJAX request Understand how to access XML data from a server response Audience This course is for someone wanting to be a professional, to be expert and confident in the entire front-end development process; those interested in building their own frameworks or being better able to learn from the source code of other well-known frameworks and libraries; and those wanting to start using frameworks that are heavily reliant on JavaScript and knowing the process flow of front-end web development. This course is for beginners to advance programmers and is suitable for intermediates who know the basics and have an idea about AJAX but want to dig deeper to know its inner workings. About The Author SkillZone: SkillZone has the simple goal of teaching complicated concepts in an effortless way. They are Johannesburg-based and create quality, easy-to-understand eLearning solutions. In today's rapidly evolving workplace, it is imperative to make sure you have the skills and expertise required to succeed. The content we offer ensures that the learning materials and delivery approach are aligned to meet intended outcomes and address your specific training needs without covering topics that may be unnecessary or irrelevant. The author's goal is to help you with in-depth learning whilst avoiding the pitfalls that he discovered the hard way. He is enthusiastic and has a lot of fun teaching and brings his personality and charisma to the teaching platform to benefit his students the most.